Assemblies of covalently cross-linked nanosheets of MoS2 and of MoS2–RGO: synthesis and novel properties. Issue 23 (25th May 2016) - Pramoda, K.; Gupta, Uttam; Ahmad, Irshad; Kumar, Ram; Rao, C. N. R.
Abstract : Covalent assemblies of MoS2 and MoS2 –RGO are synthesized by Sonogashira coupling, which exhibit high CO2 and H2 uptake as well as enhanced hydrogen evolution activity due to generated pores and more exposed edges. Abstract : We report the synthesis, characterization, gas adsorption and hydrogen evolution activity of covalently cross-linked assemblies of MoS2 and MoS2 –RGO generated by the Sonogashira coupling reaction. These assemblies show a high surface area and CO2 storage capacity comparable with some of the high surface area MOFs. MoS2 assemblies show enhanced hydrogen evolution activity compared to few-layer MoS2 .